Challenge of uncontrolled enteroatmospheric fistulas. Issue 1 (31st December 2019) - Gross, Daniel Jonathan; Smith, Michael C; Zangbar-Sabegh, Bardiya; Chao, Kenneth; Chang, Erin; Boudourakis, Leon; Muthusamy, Muthukumar; Roudnitsky, Valery; Schwartz, Tim
Abstract : Introduction: With the popularization of damage control surgery and the use of the open abdomen, a new permutation of fistula arose; the enteroatmospheric fistula (EAF), an opening of exposed intestine spilling uncontrollably into the peritoneal cavity. EAF is the most devastating complication of the open abdomen. We describe and analyze a single institution's experience in controlling high-output EAFs in patients with peritonitis. Methods: We analyzed 189 consecutive procedures to achieve and maintain definitive control of 24 EAFs in 13 patients between 2006 and 2017. EAFs followed surgery for either trauma (seven patients) or non-traumatic abdominal conditions (six patients). All procedures were mapped onto an operative timeline and analyzed for: success in achieving definitive control, number of reoperations, and feasibility of bedside procedures in the surgical intensive care unit. The end point was controlled enteric drainage through a healed abdominal wound. Results: There was a mean delay of 8.5 days (range 2–46 days) from the index operation until the EAF was identified. Most EAFs required several attempts (mean: 2.7 per patient, range 1–7) until definitive control was achieved. Multiple reoperations were then required to maintain control (mean: 13). While the most effective techniques were endoscopic (1) and proximal diversion (1), these were applicable only in select circumstances. A 'floating stoma' where the fistula edges are sutured to an opening in a temporary closure device, while technically effective, required multiple reoperations. Tube drainage through a negative pressure dressing (tube vac) required the most maintenance usually through bedside procedures. Primary closure almost always failed. Twelve of the 13 patients survived. Conclusion: An EAF is a highly complex surgical challenge. Successful source control of the potentially lethal ongoing peritonitis requires tenacity and tactical flexibility. The appropriate control technique is often found by trial and error and must be creatively tailored to the individual circumstances of the patient.